ANALYSIS OF THE MANAGEMENT OF SCHOOL OPERATIONAL ASSISTANCE FUNDS (BOS) - Sarbini; Saca Suhendi; Zahra Nur Azizah; Dede Arif Rahman Nurhakim; Muhammad Alif Ramadhan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Education plays an important role in human resource development, and the quality of education is an indicator of a nation's success. Improving the quality of education in Indonesia, especially at the elementary and secondary levels, is supported by the School Operational Assistance Program (BOS). This study examines the management of BOS funds and their impact on the quality of educational facilities and infrastructure. The methods used are library research and content analysis, with a focus on transparency, accountability, and participation in fund management. The results show that effective management of BOS funds can improve the quality of facilities and infrastructure, but there are still obstacles such as late disbursement of funds and low financial literacy. Recommendations for improving management effectiveness include financial management training and digitalization of the reporting system. This study is expected to provide insight and strategic solutions to maximize the use of BOS funds for better education quality.